Nucleophilic Reactivity of a Nitride‐Bridged Diuranium(IV) Complex: CO2 and CS2 Functionalization. Issue 12 (23rd February 2016) - Falcone, Marta; Chatelain, Lucile; Mazzanti, Marinella
Abstract: Thermolysis of the nitride‐bridged diuranium(IV) complex Cs(μ‐N)[U(OSi(O t Bu)3 )3 ]2 (1 ) showed that the bridging nitride behaves as a strong nucleophile, promoting N−C bond formation by siloxide ligand fragmentation to yield an imido‐bridged siloxide/silanediolate diuranium(IV) complex, Cs(μ‐N t Bu)(μ‐O2 Si(O t Bu)2 )U2 (OSi(O t Bu)3 )5 . Complex1 displayed reactivity towards CS2 and CO2 at room temperature that is unprecedented in f‐element chemistry, affording diverse N‐functionalized products depending on the reaction stoichiometry. The reaction of1 with two equivalents of CS2 yielded the thiocyanate/thiocarbonate complex Cs(μ‐NCS)(μ‐CS3 )[U(OSi(O t Bu)3 )3 ]2 via a putative NCS − /S 2− intermediate. The reaction of1 with one equivalent of CO2 resulted in deoxygenation and N−C bond formation, yielding the cyanate/oxo complex Cs(μ‐NCO)(μ‐O)[U(OSi(O t Bu)3 )3 ]2 . Addition of excess CO2 to1 led to the unprecedented dicarbamate product Cs(μ‐NC2 O4 )[U(OSi(O t Bu)3 )3 ]2 . Abstract : A nitride‐bridged diuranium(IV) complex rapidly reacts with CS2 and CO2 at room temperature. These transformations afford cyanate and thiocyanate species by N−C bond formation and enable the unprecedented construction of a dicarbamate product (see scheme).